1953
DOI: 10.1161/01.cir.8.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic "Activity" as Judged by the Presence of Aschoff Bodies in Auricular Appendages of Patients with Mitral Stenosis

Abstract: Left auricular appendages from 183 patients, removed at operation for mitral stenosis, have been studied with regard to presence of Aschoff bodies and endocardial thrombi. An over-all incidence of Aschoff lesions of 40 per cent was found. There was a significant decrease in Aschoff lesions in the pIesence of thrombosis. The occurrence of Aschoff bodies in the appendages is correlated with the findings in the remainder of the heart in autopsied cases.T HE DEVELOPMENT of methods for the surgical correction of rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1954
1954
1965
1965

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The author, on the basis of the clinical and pathological findings, suggested that granulomatous giant cell myocarditis was of rheumatic origin. However, Decker, Hawn and Robbins (1953) who examined the left atrial appendage in 183 cases of mitral valvotomy, and Lannigan (1959) who made a detailed study of 125 similar specimens, did not mention lesions of the type found in the present case. If giant cell myocarditis is of rheumatic origin it must be a very unusual manifestation of the disease.…”
Section: Discussionmentioning
confidence: 72%
“…The author, on the basis of the clinical and pathological findings, suggested that granulomatous giant cell myocarditis was of rheumatic origin. However, Decker, Hawn and Robbins (1953) who examined the left atrial appendage in 183 cases of mitral valvotomy, and Lannigan (1959) who made a detailed study of 125 similar specimens, did not mention lesions of the type found in the present case. If giant cell myocarditis is of rheumatic origin it must be a very unusual manifestation of the disease.…”
Section: Discussionmentioning
confidence: 72%
“…Other laboratory methods, e.g. anti-streptolysin 0 titres and the presence of C reactive protein have also shown no correlation with the histological findings (Elster and Wood, 1955). Sabiston and Follis (1952) found a correlation with the E.S.R.…”
Section: Discussionmentioning
confidence: 98%
“…Several clinico-pathological studies have been made in biopsy series (Kuschner et al, 1952;Catto et al, 1952;Biorck et al, 1952;Sabiston and Follis, 1952;McNeely et al, 1953;Manchester et al, 1955;Clark and Anderson, 1955;Elster and Wood, 1955), but no correlation has been found between the presence of histologically active lesions and the usual clinical and laboratory criteria of rheumatic activity.…”
mentioning
confidence: 99%
“…A few authors have expressed some doubts about this correlation. '9' 20 Study of material from 24 autopsies in this department and review of the literatures4' 20,22,23,40,51,52 show that Aschoff bodies in the atrial appendage are usually accompanied by evidence of rheumatic activity in the rest of the heart. Absence of atrial lesions does not necessarily Circulation, Volume It is concluded that rheumatic activity continues in many patients with mitral stenosis long after presently available laboratory tests have become negative.…”
Section: Anatomic Observationsmentioning
confidence: 99%